Optimizing Positivity Thresholds for a Risk-Adapted Screening Strategy in Colorectal Cancer Screening. Issue 8 (16th August 2021) - Lu, Ming; Wang, Le; Zhang, Yuhan; Liu, Chengcheng; Lu, Bin; Du, Lingbin; Liao, Xianzhen; Dong, Dong; Wei, Donghua; Gao, Yi; Shi, Jufang; Ren, Jiansong; et al.
Abstract : INTRODUCTION: Risk-adapted screening combining the Asia-Pacific Colorectal Screening score, fecal immunochemical test (FIT), and colonoscopy improved the yield of colorectal cancer screening than FIT. However, the optimal positivity thresholds of risk scoring and FIT of such a strategy warrant further investigation. METHODS: We included 3, 407 participants aged 50–74 years undergoing colonoscopy from a colorectal cancer screening trial. For the risk-adapted screening strategy, subjects were referred for subsequent colonoscopy or FIT according to their risk scores. Diagnostic performance was evaluated for FIT and the risk-adapted screening method with various positivity thresholds. Furthermore, a modeled screening cohort was established to compare the yield and cost using colonoscopy, FIT, and the risk-adapted screening method in a single round of screening. RESULTS: Risk-adapted screening method had higher sensitivity for advanced neoplasm (AN) (27.6%–76.3% vs 13.8%–17.3%) but lower specificity (46.6%–90.8% vs 97.4%–98.8%) than FIT did. In a modeled screening cohort, FIT-based screening would be slightly affected because the threshold varied with a reduction of 76.0%–80.9% in AN detection and 82.0%–84.4% in cost when compared with colonoscopy. By contrast, adjusting the threshold of Asia-Pacific Colorectal Screening score from 3 to 5 points for risk-adapted screening varied from an increase of 12.6%–14.1% to a decrease of 55.6%–60.1% in AN detection, with the reduction of cost from 4.2%–5.3% rising to 66.4%–68.5%. DISCUSSION: With an appropriate positivity threshold tailored to clinical practice, the risk-adapted screening could save colonoscopy resources and cost compared with the colonoscopy-only and FIT-only strategies.